2017
DOI: 10.2534/jjasnaoe.25.55
|View full text |Cite
|
Sign up to set email alerts
|

Computation and Experiment of Propeller Thrust Fluctuation in Waves for Propeller Open Water Condition

Abstract: SummaryThe prediction of the propeller load fluctuations in waves, which can cause great fluctuations of engine power and revolutions, is important for ship operations. Recently the prediction of free running model advancing in waves with real rotating propeller and rudder can be done by Computational Fluid Dynamics (CFD) technique. However, the validation of these methods is not enough and it requires huge mesh density and long computational time. The new propeller body-force prediction model (OU propeller mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Under high wave conditions, the propeller may experience a diminution of thrust and torque due to exposure of the propeller disc above the free surface [28]. This large and abrupt drop in torque may lead to engine over-speed, which is known as propeller racing [25]. The resulting change in the propeller torque is proportional to the loss of the effective disc area of the propeller.…”
Section: Diesel Enginementioning
confidence: 99%
See 1 more Smart Citation
“…Under high wave conditions, the propeller may experience a diminution of thrust and torque due to exposure of the propeller disc above the free surface [28]. This large and abrupt drop in torque may lead to engine over-speed, which is known as propeller racing [25]. The resulting change in the propeller torque is proportional to the loss of the effective disc area of the propeller.…”
Section: Diesel Enginementioning
confidence: 99%
“…The most important outcome of this study was the conclusion that the response of the system, including the engine power, propeller rotation speed and torque, can be determined only through the use of a coupled simulation model when realistic engine and propeller models are employed. Following this, Tokgoz et al [25] carried out experimental and numerical analyses of twin propellers operating behind a hull in regular head wave conditions. They concluded that in regular waves, and at an encounter frequency close to its mean value in calm water, the propeller thrust undergoes harmonic oscillation, with a relatively small amplitude; however, when the propeller blade approaches the water surface and ventilation occurs, the propeller thrust radically changes and decreases.…”
Section: Introductionmentioning
confidence: 99%